Novel navigation technique for the endodontic treatment of a molar with pulp canal calcification and apical pathology. (23rd June 2017) - Shi, Xilin; Zhao, Shiyong; Wang, Weidong; Jiang, Qianzhou; Yang, Xuechao
Abstract: Apical periodontitis, the inflammation of periapical tissue, commonly requires root canal treatment to achieve apical healing. However, if it is accompanied by pulp canal calcification, the treatment becomes complicated, and locating the root canal can be challenging. This case report describes a novel approach for treating a molar with pulp canal calcification and apical pathology. Due to the risk of perforation during treatment, a digitally printed template was used to assist in accurately locating the root canal. After six months, the patient was asymptomatic and the periradicular radiolucency was gradually reducing in size.